Elucidation of the di-c-glycosylation steps during biosynthesis of the antitumor antibiotic, kidamycin - Heo, Kyung Taek; Lee, Byeongsan; Jang, Jae-Hyuk; Hong, Young-Soo (Frontiers in Bioengineering and Biotechnology, 2022)
Kidamycins belong to the pluramycin family of antitumor antibiotics that contain di-C-glycosylated angucycline. Owing to its interesting biological activity, several synthetic derivatives of kidamycins are currently being developed. However, the synthesis of these complex structural compounds with unusual C-glycosylated residues is difficult. In the kidamycin-producing Streptomyces sp. W2061 strain, the genes encoding the biosynthetic enzymes responsible for the structural features of kidamycin were identified. Two glycosyltransferase-coding genes, kid7 and kid21, were found in the kidamycin biosynthetic gene cluster (BGC). Gene inactivation studies revealed that the subsequent glycosylation steps occurred in a sequential manner, in which Kid7 first attached N,N-dimethylvancosamine to the C10 position of angucycline aglycone, following which Kid21 transferred an anglosamine moiety to C8 of the C10-glycosylated angucycline. Therefore, this is the first report to reveal the sequential biosynthetic steps of the unique C-glycosylated amino-deoxyhexoses of kidamycin. Additionally, we confirmed that all three methyltransferases (Kid4, Kid9, and Kid24) present in this BGC were involved in the biosynthesis of these amino-deoxyhexoses, N,N-dimethylvancosamine and anglosamine. Aglycone compounds and the mono-C-glycosylated compound obtained in this process will be used as substrates for the development of synthetic derivatives in the future.